The European Approach to the Use of Artificial Intelligence for Sustainable Development. - España Pérez, José Alberto (Oxford University Press, 2025)
Sustainable development in AI is an essential element to ensure that this technology fosters a beneficial future from environmental, social, and economic perspectives. Indeed, the multiple applications of AI have great potential for achieving the UN Sustainable Development Goals. Accordingly, the EU has enacted the Artificial Intelligence Act, a legal framework adopted in 2024 that incorporates (to varying degrees) the principles of sustainable development in the use of AI systems. To this end, the legislative technique is fundamentally based on a risk management approach. The law classifies AI systems according to their risk levels and assigns different requirements and obligations accordingly. Thus, this article examines how the European law addresses the advancement of AI in its contribution to sustainability.

El desarrollo sostenible en la inteligencia artificial (IA) constituye un elemento esencial para lograr que esta tecnología asegure un futuro beneficioso desde la perspectiva medioambiental, social y económica. De hecho, las múltiples aplicaciones de la IA encierran un gran potencial para cumplir con los Objetivos de Desarrollo Sostenible. Bajo esta perspectiva la Unión Europea ha promulgado la denominada Ley de Inteligencia artificial. Un reciente marco legal que incorpora (en diferente amplitud) los postulados del desarrollo sostenible para el desarrollo de los sistemas de inteligencia artifician. Para ello, la técnica legislativa se basa fundamentalmente en un enfoque de gestión de riesgos. La ley clasifica los sistemas de IA según sus niveles de riesgo y asigna diferentes requisitos y obligaciones en consecuencia. Así, este trabajo examina cómo la legislación europea aborda el avance de la IA en su contribución a la sostenibilidad.
El trabajo debe estar embargado hasta el 1 de septiembre de 2026, atendiendo a la política de la editorial (adjunta correo con autorización)
Keywords: Desarrollo sostenible; Inteligencia artificial; Sustainability; Unión Europea; Objetivos de Desarrollo Sostenible; Sustainable development; Artificial intelligence; Sustainable development goals; European Union